Flow regulation is associated with riverine soil seed bank composition within an agricultural landscape: potential implications for restoration. (3rd July 2012) - Greet, Joe; Cousens, Roger D.; Webb, J. Angus; Prober, Suzanne
Abstract Questions Does altered flow timing affect seed bank dynamics within river margins of agricultural areas? Are seed banks of degraded riparian zones important for contributing to native riverine plant diversity? Location Murray‐Darling Basin, SE Australia. Methods We surveyed the seed banks of five lowland rivers, three of which have large dams that alter the seasonal timing of flow peaks. Three sites on each river with a remnant native overstorey were selected and classified into three levels of regulation based on the extent to which their seasonal flow timing was altered. Soil samples were collected from each site, and seed bank composition determined using the seedling emergence method. We also experimentally tested the effect of seasonal timing of flow peaks on germination by wetting seed bank subsamples in both spring and autumn. Results More than 28 000 seedlings from 115 taxa germinated from the seed bank samples; 262 taxa had previously been recorded in the extant vegetation. In general, seed bank and extant vegetation compositions were dissimilar, and the seed banks surveyed were dominated by ruderal (and often exotic) species. More seedlings and taxa (both native and exotic) germinated from the seed banks of regulated sites than unregulated sites. Spring wetting favoured the germination of some native species, while exotic grass taxa germinated in greater numbers in autumn. Conclusions Our results suggest that flow regulation affects the composition of riverine seed banks. This is likely to be driven by changes in the extant vegetation, and altered patterns of germination and water‐borne seed dispersal (hydrochory). Regardless, the role of seed banks in degraded riverine systems in promoting native plant diversity may be limited. In particular, riparian woody species often do not develop persistent soil seed banks; rather, their recruitment may rely on newly released seeds being dispersed and deposited at appropriate times for germination. Our study corroborates previous research suggesting that flow regulation affects riverine seed bank dynamics, and that natural seasonal flow peaks are important for the persistence of some native riverine plant species.